Elevation of CD56brightCD16- lymphocytes in MDR pulmonary tuberculosis - Mousavi, Tahereh; Farnia, Parisa; Tajik, Nader; Soofi, Mahbubeh (Iranian journal of immunology, 2010)
Protective immune responses induced in the majority of people infected with Mycobacterium tuberculosis enable them to control TB infection. The aim of this study was to investigate CD56 and CD16 positive peripheral blood mononuclear cells (PBMCs) and leukocyte subsets from multi-drug resistant pulmonary tuberculosis (MDR-TB), and compare them with nonresistant (NR) TB patients and healthy controls. 13 MDR-tuberculosis patients, 20 NR-TB individuals and 40 healthy subjects were included. Peripheral blood mononuclear cells were double stained with fluorochrome conjugated antibodies against CD56 and CD16 cell surface markers. The phenotype of positive cells was then analyzed by flow cytometry and the percentages of CD56+ CD16+, CD56- CD16+, CD56dimCD16+/-, and CD56brightCD16+/- subsets were calculated. There was a significant decline in the percentage of CD56+CD16+ lymphocytes in both MDR and NR-TB patients compared with healthy controls. We also observed lower proportions of CD56dim/brightCD16+ in addition to higher percentages of CD56dim/brightCD16- subsets in all TB patients (p<0.05). In MDR-TB, our findings demonstrated a distinct phenotypic feature with increased levels of CD56brightCD16- in comparison with both NR-TB and healthy subjects. Considering the function of CD56/CD16 expressing cells in TB, we suggest that phenotypic characteristics of PBMCs in MDR-TB may correlate with their status of drug resistance and probably with their high mortality rates.